Development of the analysis method of the influence of the economic factor on migration (on the example of Akmola region) - Ivan Georgievich Plachinta (Наука. Инновации. Технологии, 2022)
This article is devoted to the study of the links between the socio-economic efficiency of the development of the region and the migration activity of the population. The goal of the work is to develop a method for studying the influence of the economic factor on migration, by the form of a mathematical model. For this, there were used conventional methods of gravity modeling, scaling and criterial estimation. The purpose of the study is to identify the link between migration and socio-economic efficiency of the region through the use of gravity modeling. Akmola region, the region - where there was a steady trend of outflow of population was taken as the object of research. The method of the gravity modeling directed not on forecasting of migration, but on the formation of its pattern with the existing set of socio-economic indicators. As part of the study, statistical data were processed since 2000. According to the results of the study, the obtained gravity model completely relected the existing migration situation in the regions, and also allowed to identify administrative subjects, where it is necessary to study intra-district migration for the presence of centripetal movements of the population. At the end of the article, the conclusion and perspective directions of further studies of the inluence of the economic factor using gravity models are indicated.